Dissecting the Physiological Function of Plant Glyoxalase I and Glyoxalase I-Like Proteins - Schmitz, Jessica; Rossoni, Alessandro W.; Maurino, Veronica G. (Frontiers in Plant Science, 2018)
The Arabidopsis genome annotation include 11 glyoxalase I (GLXI) genes, all encoding for protein members of the vicinal oxygen chelate (VOC) superfamily. The biochemical properties and physiological importance of three Arabidopsis GLXI proteins in the detoxification of reactive carbonyl species has been recently described. Analyses of phylogenetic relationships and conserved GLXI binding sites indicates that the other eight GLXI genes (GLXI-like) do not encode for proteins with GLXI activity. In this perspective article we analyse the structural features of GLXI and GLXI-like proteins, and explore splice forms and transcript abundance under abiotic stress conditions. Finally, we discuss future directions of research on this topic with respect to the substrate identification of GLXI and GLXI-like proteins and the need of reliable quantitative measurements of reactive carbonyl species in plant tissues.